Interviews in qualitative research - King, Nigel; Horrocks, Christine; Brooks, Joanna (SAGE Publications Ltd, 2019)
This dynamic user-focused book will help you get the data you want from your interviews. It provides practical guidance regarding technique, gives top tips from real world case studies and shares achievable checklists and interview plans. Whether you are doing interviews in your own research or using other researchers' data, this book will tell you everything you need to know about designing, planning, conducting and analyzing quality interviews. Written in clear, jargon-free terminology and with coverage of practical, theoretical and philosophical issues all grounded in examples from real interviews, this is the ideal guide for new and experienced researchers alike.